Ecotype Variation of Methyl Eugenol Content in Tea Tree (Melaleuca alternifolia and Melaleuca linariifolia). Issue 11 (27th October 2017) - Shepherd, Mervyn; Savins, Dale; Dowell, Ashley; Morrow, Samantha; Allen, Gareth; Southwell, Ian
Abstract : Methyl eugenol is a natural phenylpropanoid compound found in a wide range of plants used for food, flavouring, cosmetics, and health‐care. As a suspected rodent carcinogen, methyl eugenol may also be harmful to humans when present in significant concentrations. Consequently, its level has been restricted in some foodstuffs and cosmetics for some markets. In order to assess the potential to breed uniformly low methyl eugenol cultivars for an essential oil crop, tea tree, the source of 'Oil of Melaleuca, terpinene‐4‐ol type', we examine levels in individual trees ( n  =   30) from two geographic regions and six terpene chemotypes. Overall, methyl eugenol levels were low in this species (Mean [SD] 354 [239] ppm, n  =   30), much lower than levels predicted to be of toxicological concern. Within each chemotype, there was a lack of evidence for correlations between terpenoid constituents and methyl eugenol levels. Further support for the independence of methyl eugenol and terpene biosynthesis was evident from similar mean levels in selected (Mean [SD] 586 [339] ppm, n  =   12) and undomesticated Melaleuca alternifolia trees (Mean [SD] 480 [299] ppm, n  =   5) with terpinen‐4‐ol type oils. By contrast, methyl eugenol level varied by geographic origin and chemotype. Trees from the upland region, where there is a prevalence of terpinolene type trees, had lower average methyl eugenol levels than trees from the coastal region, where there is a prevalence of terpinen‐4‐ol and 1, 8‐cineole type trees. Abstract :